2018
DOI: 10.1111/jog.13807
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of dydrogesterone for treatment of dysmenorrhea: An open‐label multicenter clinical study

Abstract: Aims: Dydrogesterone is a retro-progesterone preparation widely used for over a half century. We sought to evaluate the efficacy and safety of dydrogesterone in Japanese women with dysmenorrhea. Methods: This study was conducted as an open-label, single-arm, multicenter study. One dydrogesterone 5-mg tablet (Duphaston) was administered orally twice daily for 21 days from the 5th to 25th day of each menstrual cycle. A total of 44 (safety analysis) and 31 patients (efficacy analysis) were enrolled. Total dysmeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
(12 reference statements)
2
6
0
Order By: Relevance
“…29 In agreement with the present study, dydrogesterone was well tolerated although the trial reported a higher incidence of ADRs than this survey (31.8% versus 11.9%) and a higher incidence of the most common AE-abnormal uterine bleeding (29.5%; versus 5.1%). 29 These findings possibly reflect differences in the methodology for recording AEs, since in the Taniguchi study each patient recorded This real-world observational study has a number of limitations which need to be acknowledged. Firstly, it did not include a control group and so all conclusions about the relative effectiveness and safety of dydrogesterone must be guarded.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…29 In agreement with the present study, dydrogesterone was well tolerated although the trial reported a higher incidence of ADRs than this survey (31.8% versus 11.9%) and a higher incidence of the most common AE-abnormal uterine bleeding (29.5%; versus 5.1%). 29 These findings possibly reflect differences in the methodology for recording AEs, since in the Taniguchi study each patient recorded This real-world observational study has a number of limitations which need to be acknowledged. Firstly, it did not include a control group and so all conclusions about the relative effectiveness and safety of dydrogesterone must be guarded.…”
Section: Discussionsupporting
confidence: 91%
“…A recent open‐label trial of Japanese patients with dysmenorrhea reported that dydrogesterone significantly reduced total dysmenorrhea VAS scores and dysmenorrhea‐related pain symptoms 29 . In agreement with the present study, dydrogesterone was well tolerated although the trial reported a higher incidence of ADRs than this survey (31.8% versus 11.9%) and a higher incidence of the most common AE—abnormal uterine bleeding (29.5%; versus 5.1%) 29 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Among reproductive aged women, dysmenorrhea is one of the most common gynecologic problems. [5][6][7] Hypothesizing an association between dysmenorrhea, abnormal uterine contractility and failed placentation, we conducted a prospective cohort study and extracted the background lifestyle and gynecological characteristics for HDP (Table 1). Notably, we found that the history of dysmenorrhea in early adulthood increased the risk of developing HDP.…”
Section: Discussionmentioning
confidence: 99%
“…Dysmenorrhea is defined as pelvic or low‐back pain during the menstrual period in interference with activities of daily living. Among reproductive aged women, dysmenorrhea is one of the most common gynecologic problems 5–7 . Hypothesizing an association between dysmenorrhea, abnormal uterine contractility and failed placentation, we conducted a prospective cohort study and extracted the background lifestyle and gynecological characteristics for HDP (Table 1).…”
Section: Discussionmentioning
confidence: 99%